2017
DOI: 10.4254/wjh.v9.i14.667
|View full text |Cite
|
Sign up to set email alerts
|

Protein tolerance to standard and high protein meals in patients with liver cirrhosis

Abstract: AIMTo investigate the plasma amino acid response and tolerance to normal or high protein meals in patients with cirrhosis.METHODSThe plasma amino acid response to a 20 g mixed protein meal was compared in 8 biopsy-proven compensated cirrhotic patients and 6 healthy subjects. In addition the response to a high protein meal (1 g/kg body weight) was studied in 6 decompensated biopsy-proven cirrhotics in order to evaluate their protein tolerance and the likelihood of developing hepatic encephalopathy (HE) followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
2
14
2
2
Order By: Relevance
“…Of special importance are hyperammonaemia, hypoalbuminaemia, low BCAA and high aromatic amino acids, as well as decreased urea and glucose levels. Decreased blood plasma concentrations of BCAA and increased concentrations of aromatic amino acids in blood plasma found in cirrhotic rats are characteristic for subjects with liver cirrhosis, but not for acute liver injury . The BCAA deficiency and their positive effects on protein metabolism in muscles provide a clear rationale to recommend their supplementation in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Of special importance are hyperammonaemia, hypoalbuminaemia, low BCAA and high aromatic amino acids, as well as decreased urea and glucose levels. Decreased blood plasma concentrations of BCAA and increased concentrations of aromatic amino acids in blood plasma found in cirrhotic rats are characteristic for subjects with liver cirrhosis, but not for acute liver injury . The BCAA deficiency and their positive effects on protein metabolism in muscles provide a clear rationale to recommend their supplementation in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 89%
“…HOLEČEK and VOdEnIČaROVOVÁ characteristic for subjects with liver cirrhosis, 25,26 but not for acute liver injury. 27 The BCAA deficiency and their positive effects on protein metabolism in muscles provide a clear rationale to recommend their supplementation in patients with cirrhosis.…”
mentioning
confidence: 96%
“…skeletal muscle. 18 A characteristic pattern of plasma amino acids has been described in cirrhotic subjects [4][5][6][7][8][9]19,20 and metabolic and biochemical differences have been shown between stable and unstable cirrhotics. 4 In this study we observed the characteristic pattern of increased concentration of the aromatic amino-acids (AAA) tyrosine, phenylalanine and tryptophan, and decreased concentration of branched-chain amino acids (BCAA) leucine, isoleucine and valine.…”
Section: Discussionmentioning
confidence: 99%
“…Allenfalls bei Patienten mit HE und oberer gastrointestinaler Blutung kann für drei bis fünf Tage auf eine Proteinzufuhr verzich-tet werden [584]. Das Auftreten weiterer HE-Episoden wird durch eine normale Proteinkost unter Fortführung einer HE-Standardtherapie in der Regel nicht begünstigt [117,570].…”
Section: Kommentarunclassified